THE USE OF SWEAR WORDS AND ITS RELATIONSHIP WITH TABOO WORDS IN FIST FIGHT MOVIE - Komang Dian Puspita Candra; Ni Putu Cahya Megandari (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTPeople use language to interact and understand each other. In conversation, people notalways use polite word but also taboo word for the example to support the situation likefriendliness, familiarity or identity among communities. The uses of taboo words also toexpress a strong emotion feeling and it familiar as swear words. Swear words are the informalwords that are used by people to express their emotion in terrible situation. The existence ofswear words can be seen from various sources such as in movies, song lyrics, and televisionshows. This research concern with the use of swears words and its relationship with taboowords in Fist Fight movie. This movie was chosen as data source because there are manyswearing words uttered by the characters. This research were analyzed qualitatively andquantitatively using theories from Batistela (2015) to find the types of taboo words and theoryproposed by Swan (1995) to find the types of swearing words. The result show that all typesof strong and weak swear word used by the character depends on the situation. Exclamation ofannoyance is dominantly appear in strong swear word and exclamation of surprised is dominantused in weak swear word. All of strong swear word in Fist fight movie are considered as tabooword that refer to epithets, profanity, vulgarity and obscenity types. There are only a few ofweak swear words that are considered as taboo word in English.Keywords: swear word, taboo word, sociolinguistics, movieABSTRAKBahasa digunakan untuk berinteraksi dalam masyarakat. Dalam melangsungkanpercakapan, bahasa yang digunakan tidak selalu sopan terkadang juga menggunakan bahasatabu untuk mendukung situasi pertemanan, keakraban atau sebagai identitas antarakomunitas. Penggunaan bahasa tabu juga dapat digunakan untuk mengekspresikan perasaanyang lebih dikenal dengan “swear words”. Swear word merupakan kata-kata dalam bentukinformal yang digunakan untuk mengekspresikan perasaan dalam keadaan yang buruk.Keberadaan swear word dapat dilihat dari beragam sumber seperti film, lirik lagu, acara tv.Penelitian ini focus kepada penggunaan swear word dan hubungannya dengan bahasa tabudalam film Fist Fight. Film ini dipilih sebagai sumber data karena banyaknya swear wordyang digunakan oleh karakter. Penelitian ini dianalisis secara kualitatif dan kuantitatifmenggunakan teori dari Batistela (2015) tentang bahasa tabu dan teori dari Swan (1995)tentang swear word. Hasil dari penelitian ini yaitu seluruh tipe dari strong swear word andweak swear word ditemukan dalam film. Tipe swear word yang paling banyak muncul adalahexclamation of annoyance, dan tipe yang paling banyak muncul di weak swear word adalahexclamation of surprised. Seluruh tipe strong swear word termasuk dalam bahasa tabu yaitujenis epithets, profanity, vulgarity dan obscenity, namun tidak semua jenis weak swear wordtermasuk dalam kategori bahasa tabu.